Method for preparing sodium-ion battery hard carbon negative electrode material by modifying industrial waste activated carbon
By modifying industrial waste activated carbon into a hard carbon anode material for sodium ion batteries, the problem of hard carbon production relies on coconut shells is solved, and the recycling of waste activated carbon and the improvement of hard carbon performance is achieved.
Patent Information
- Application Number
- CN202510139931.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2045-02-08
AI Technical Summary
The production of existing sodium ion battery hard carbon anode materials depends on coconut shells, resulting in insufficient raw material sources, high costs, poor performance, and difficult to effectively utilize industrial waste activated carbon in traditional processes.
By using industrial waste activated carbon as a precursor, combining polymer and water or organic solvents, hard carbon negative electrode materials for sodium ion batteries are prepared by mixing, ball milling, drying, medium and low temperature pretreatment and high temperature carbonization.
The recycling of waste activated carbon is realized, the dependence of hard carbon on coconut shells is reduced, the yield and electrochemical performance of hard carbon is improved, production costs are reduced, and resource waste is reduced.
Smart Images

Figure CN119569036A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a hard carbon negative electrode material for a battery, in particular to a method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon. Background Art
[0002] In recent years, batteries have played an increasingly important role in people's production and life. Compared with traditional lithium-ion batteries, sodium-ion batteries have many advantages such as richer raw material sources, lower costs, better low-temperature performance, and higher safety, which makes sodium-ion batteries have broad application prospects in energy storage and low-speed electric vehicles.
[0003] Studies have shown that among the structural materials of sodium-ion batteries, hard carbon is the negative electrode material with the most application potential for sodium-ion batteries, and using biomass as a precursor to prepare hard carbon is the most widely used method for industrial preparation of hard carbon negative electrode materials for sodium-ion batteries at this stage.
[0004] However, the raw materials for preparing hard carbon materials are mainly coconut shells produced in Southeast Asia. The distance is long and the transportation cost is too high. According to the survey results, the carbon content of biomass is about 20%. Taking into account the processing loss, the mass ratio of biomass to hard carbon output is about 6:1. In other words, the negative electrode material required for the production of 1GWh sodium-ion battery requires about 9,000 tons of coconut shells, while the total annual output of coconut shells in the world is only more than 1 million tons. In addition, coconut shells are also used as raw materials for activated carbon and other purposes. Therefore, there are fewer coconut shells that can be used for hard carbon production. Therefore, according to the current hard carbon processing technology, there are major problems with the source of raw materials, resulting in high hard carbon costs and unfavorable large-scale production.
[0005] In addition, studies have shown that the hard carbon negative electrode produced by traditional processes has problems such as low specific capacity, low first coulombic efficiency, and poor cycle performance, which limits the improvement of the overall energy density of sodium-ion batteries.
[0006] Therefore, how to reduce the dependence of hard carbon materials on coconut shells, reduce the production cost of hard carbon materials, and improve the performance of hard carbon negative electrode materials for sodium ion batteries are technical problems that technicians in this field urgently need to solve.
[0007] As an alternative, there are reports showing that hard carbon can be prepared using agricultural waste and solid waste as hard carbon sources. However, the hard carbon prepared using agricultural waste and solid waste as precursors has problems such as poor uniformity, unstable specific capacity, and high ash content, which makes it difficult to use in sodium-ion batteries.
[0008] Activated carbon is another carbon material that is completely different from hard carbon. It is widely and extensively used in industry as an adsorbent, especially in the electronics, shoemaking, printing and other waste gas treatment fields. Activated carbon is often used to adsorb organic waste gas generated during the processing. However, due to its strong adsorption capacity and lack of desorption ability, it is difficult to recycle used activated carbon for secondary use. It is often treated as industrial waste, which imposes a considerable burden on enterprises and also causes a waste of activated carbon resources.
[0009] Since activated carbon cannot be used directly as the negative electrode material of sodium ion batteries, if industrial waste activated carbon can be used as a precursor of hard carbon materials, it will greatly reduce the dependence of hard carbon on coconut shells, thereby reducing the production cost of hard carbon, and can achieve the recycling of waste activated carbon, reduce the processing burden of related enterprises, and reduce the waste of activated carbon resources.
[0010] For example, the patent with publication number CN117894959A discloses a method for preparing an activated carbon negative electrode material for a sodium ion battery, specifically disclosing that activated carbon is treated with aluminum nitrate to prepare an alumina-modified activated carbon, which can be used as a negative electrode material for a sodium ion battery.
[0011] For example, the patent with publication number CN117208888A discloses a process for preparing a hard carbon negative electrode material for a sodium ion battery, and specifically discloses that the hard carbon material for a sodium ion battery is prepared by modifying activated carbon with resorcinol formaldehyde resin.
[0012] However, the aforementioned existing processes all use unused activated carbon as a precursor to prepare hard carbon, and do not solve the problem of resource waste and heavy processing burden on enterprises caused by discarded activated carbon. There are currently no reports showing that industrial waste activated carbon can be used as a precursor of hard carbon materials for sodium ion batteries. Whether it can be used as a precursor of hard carbon materials and how it should be handled during the application process are unknown to technicians. Summary of the invention
[0013] In order to solve the above technical problems, the present invention provides a method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon. The method of the present invention is simple, environmentally friendly, can realize the waste utilization of waste activated carbon, and the prepared hard carbon has the characteristics of high yield, good electrochemical performance and low cost.
[0014] One of the technical solutions of the present invention: Provided is a method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon. The method uses industrial waste activated carbon as a raw material, a high molecular polymer as a modifier, and water or an organic solvent as a solvent. The method is performed by first mixing, then medium-low temperature pretreatment, and finally high-temperature carbonization to obtain the hard carbon negative electrode material for a sodium ion battery.
[0015] Preferably, the method for preparing a sodium ion battery hard carbon negative electrode material by modifying industrial waste activated carbon comprises the following steps: S1. Take industrial waste activated carbon and high molecular polymer for use; S2. mixing industrial waste activated carbon, a polymer and a solvent to obtain a mixture; S3. The mixture of S2 is placed in a ball mill and mixed to obtain a ball mill material; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated in an air atmosphere at 300-600°C for 1-4h to obtain a pretreated material; S6. The pretreated material of S5 is transferred to a tubular furnace, and carbonized for 0.5-10 h in an inert gas atmosphere at 1000-1400° C., and then taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0016] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the industrial waste activated carbon is waste activated carbon produced in the field of waste gas treatment in the electronics industry, the shoemaking industry or the printing industry.
[0017] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the high molecular polymer is one or any combination of polyvinyl alcohol, polyethylene glycol, polypropylene or polyethylene terephthalate.
[0018] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the organic solvent is hexafluoroacetone.
[0019] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the mixing mass ratio of the industrial waste activated carbon and the high molecular polymer is 1:0.1-30.
[0020] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the mixing mass ratio of the total mass of the industrial waste activated carbon and the high molecular polymer to the solvent is 1:0.5-2.
[0021] Preferably, in the aforementioned method for modifying industrial waste activated carbon to prepare a hard carbon negative electrode material for a sodium ion battery, the rotation speed of the ball mill is 300-500 rpm, and the ball milling time is 1-3 h.
[0022] The second technical solution of the present invention: Provided is a sodium ion battery hard carbon negative electrode material prepared according to the aforementioned method.
[0023] The third technical solution of the present invention: Provided is an application of the aforementioned hard carbon negative electrode material as a hard carbon negative electrode material for a sodium ion battery.
[0024] Beneficial effects of the present invention: 1. The hard carbon negative electrode material processing technology of the present invention mainly includes the steps of mixing, medium and low temperature pretreatment and high temperature carbonization. The process is simple, easy to implement industrially, and can be widely promoted.
[0025] 2. The hard carbon negative electrode material of the present invention is prepared with industrial waste activated carbon as a precursor, which solves the problem of difficult treatment and waste of resources of waste activated carbon and realizes waste utilization; on the other hand, it greatly reduces the dependence of hard carbon on coconut shells and reduces the production cost of hard carbon.
[0026] 3. The hard carbon negative electrode material of the present invention can be processed by using water-soluble polymers and water as a solvent, so that better environmental protection effects can be achieved during the processing.
[0027] 4. The hard carbon precursor of the present invention is waste activated carbon, and the adsorbed substance therein can be used as a sealing agent in the present invention to seal the surface pores of the activated carbon, thereby improving the sealing effect. Therefore, compared with using new activated carbon as a precursor, the hard carbon prepared using waste activated carbon in the present invention has better electrochemical properties.
[0028] 5. The process of the present invention first performs medium-low temperature pretreatment in an air atmosphere, so that the adsorbent in the waste activated carbon can be better carbonized and closed pores are effectively formed, thereby further improving the electrochemical properties of the hard carbon; at the same time, this process can introduce oxygen-containing functional groups at the sealing sites, further improving the yield and electrochemical properties of the hard carbon. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Attached Figure 1 It is the charge and discharge curve diagram of the hard carbon negative electrode material of the control group 1-2 and the embodiment 1-7. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0031] The industrial waste activated carbon used in the embodiment of the present invention is waste activated carbon generated in the fields of electronics industry, shoemaking industry and printing industry.
[0032] The activated carbon used in the embodiment of the present invention is a porous adsorbent. After being used in the electronics industry, shoemaking industry, printing industry and other fields, the substances it adsorbs are mainly volatile organic waste gases such as VOCs, mainly including organic waste gases such as aliphatic hydrocarbons, aromatic compounds, ketones and esters. These substances will escape or carbonize during the pre-oxidation and high-temperature carbonization process and become part of the hard carbon negative electrode.
[0033] Embodiments of the present invention Example 1 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 25g of polyvinyl alcohol for later use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 125 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 2 h in an air atmosphere at 400 ° C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, carbonized for 2 h in an argon atmosphere at 1400°C, taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0034] Example 2 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 100g of polyvinyl alcohol for later use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 200 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated at 450°C in an air atmosphere for 2h to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, and carbonized for 5 h in an argon atmosphere at 1200° C., and then taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0035] Example 3 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 500g of polyvinyl alcohol for later use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 600 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 2 h in an air atmosphere at 500 ° C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, and carbonized for 4 h in an argon atmosphere at 1300°C, and then taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0036] Example 4 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 1000g of polyvinyl alcohol for later use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 1100 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 2 h in an air atmosphere at 300 ° C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, carbonized for 5 h in an argon atmosphere at 1000° C., taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0037] Example 5 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 500g of polyethylene terephthalate for use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 600 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 2 h in an air atmosphere at 400 ° C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, carbonized for 5 h in an argon atmosphere at 1400° C., taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0038] Example 6 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 10g of polyethylene glycol for later use; S2. All industrial waste activated carbon and polyethylene glycol were mixed with 55 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 300 rpm and milled for 3 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 4 hours in an air atmosphere at 300°C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, carbonized for 10 h in a nitrogen atmosphere at 1000° C., taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0039] Example 7 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, the steps are as follows: S1. Take 100g of industrial waste activated carbon and 3000g of polypropylene for standby use; S2. All industrial waste activated carbon and polypropylene were mixed with hexafluoroacetone 6200g to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 500 rpm and milled for 1 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated in an air atmosphere at 600°C for 1h to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, and carbonized for 0.5 h in a nitrogen atmosphere at 1400° C., and then taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0040] Control group 1 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon. In this control group, no modified organic matter is added, and the remaining steps remain unchanged. The preparation steps are as follows: S1. Take 100g of industrial waste activated carbon for later use; S2. All the industrial waste activated carbon and 600 g of water were mixed to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated for 2 h in an air atmosphere at 400 ° C to obtain a pretreated material; S6. The pretreated material of S5 was transferred to a tubular furnace, carbonized for 2 h in an argon atmosphere at 1400°C, taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0041] Control group 2 A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon. Control group 2 did not undergo pre-oxidation treatment, and the remaining steps remained unchanged. The preparation steps are as follows: S1. Take 100g of industrial waste activated carbon and 25g of polyvinyl alcohol for later use; S2. All the industrial waste activated carbon and polyvinyl alcohol were mixed with 125 g of water to obtain a mixture; S3. The mixture of S2 was placed in a ball mill at 400 rpm and milled for 2 h to obtain a ball mill; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a tubular furnace and carbonized for 2 hours in an argon atmosphere at 1400°C. The dried material is taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
[0042] The charge and discharge performance of the hard carbon materials prepared by the control group 1-2 and the example 1-7 are shown in the following table: sample Modified organic matter type Mass ratio of activated carbon to organic matter Pre-oxidation temperature (℃) High temperature carbonization temperature (℃) Charge specific capacity (mAh / g) Discharge specific capacity (mAh / g) First coulombic efficiency (%) Control group 1 none / 400 1400 26.8 111.7 24.0 Control group 2 Polyvinyl alcohol 1:0.25 / 1400 114.3 170.4 67.1 Example 1 Polyvinyl alcohol 1:0.25 400 1400 168.1 209.2 80.3 Example 2 Polyvinyl alcohol 1:1 450 1200 191.8 230.0 83.4 Example 3 Polyvinyl alcohol 1:5 500 1300 210.4 241.3 87.2 Example 4 Polyvinyl alcohol 1:10 300 1000 207.1 249.7 82.9 Example 5 Polyethylene terephthalate 1:5 400 1400 220.7 252.4 87.4 Example 6 Polyethylene glycol 1:0.1 300 1000 136.5 150.9 90.4 Example 7 Polypropylene 1:30 600 1400 221.2 265.6 83.3 It can be seen from the above table that the charge and discharge specific capacity of the industrial waste activated carbon in the control group 1 is relatively low, and the first coulombic efficiency is only 24.0%. The charge and discharge performance of the samples in the control group 2 that have not undergone pre-oxidation treatment is worse than that of the samples that have undergone pre-oxidation treatment in Example 1, and the first coulombic efficiency is also lower.
[0043] The hard carbon negative electrode material prepared by the process of the present invention has high charge and discharge performance, and the first coulomb efficiency is higher than 80%.
[0044] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon, characterized in that: The steps include: S1. Take industrial waste activated carbon and high molecular polymer for use; S2. mixing industrial waste activated carbon, a polymer and a solvent to obtain a mixture; S3. The mixture of S2 is placed in a ball mill and mixed to obtain a ball mill material; S4. Dry the ball mill material of S3 to obtain dry material; S5. The dried material of S4 is placed in a muffle furnace and pretreated in an air atmosphere at 300-600°C for 1-4h to obtain a pretreated material; S6. The pretreated material of S5 is transferred to a tubular furnace, and carbonized for 0.5-10 h in an inert gas atmosphere at 1000-1400° C., and then taken out and cooled to obtain a hard carbon negative electrode material for a sodium ion battery.
2. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The industrial waste activated carbon is waste activated carbon produced in the field of waste gas treatment in the electronics industry, shoemaking industry or printing industry.
3. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The high molecular polymer is one of polyvinyl alcohol, polyethylene glycol, polypropylene or polyethylene terephthalate.
4. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The organic solvent is hexafluoroacetone.
5. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The mixing mass ratio of the industrial waste activated carbon and the high molecular polymer is 1:0.1-30.
6. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The mixing mass ratio of the total mass of the industrial waste activated carbon and the high molecular polymer to the solvent is 1:0.5-2.
7. The method for preparing a hard carbon negative electrode material for a sodium ion battery by modifying industrial waste activated carbon according to claim 1, characterized in that: The rotation speed of the ball mill is 300-500 rpm, and the ball milling time is 1-3 h.
8. A hard carbon negative electrode material for a sodium ion battery, characterized in that: Prepared according to the method according to any one of claims 1 to 7.
9. Application of a hard carbon negative electrode material as a hard carbon negative electrode material for a sodium ion battery, characterized in that: The hard carbon negative electrode material is prepared according to the method according to any one of claims 1-7.
Citation Information
Patent Citations
Manufacturing process of hard carbon negative electrode material for sodium ion battery
CN117208888A
Activated carbon negative electrode material for sodium ion battery and preparation method of activated carbon negative electrode material
CN117894959A
Negative electrode for lead-carbon battery and preparation and application thereof
CN109841798A
Method for preparing hard carbon negative electrode material by using waste thermosetting plastic
CN116102012A
Method for preparing carbon material based on invalid activated carbon and application of carbon material
CN116514102A
Cited By
Hard carbon material and preparation method and application thereof
CN120004269A
A hard carbon material, its preparation method and application
CN120004269B